Penerapan Keluarga Sakinah oleh Pasangan Suami Istri sebagai Keluarga Binaan di KUA Wonokromo Surabaya - Basyarahil, Ramzy Muhammad; Ashari, Winning Son (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2024)
The aim of this research is to determine the content of marriage guidance received from the Wonokromo Religious Affairs Office (KUA), to understand the reasons why prospective couples participate in marriage guidance at KUA Wonokromo, and to ascertain the practice of the values of a Sakinah family by married couples under the mentorship of KUA Wonokromo. The research method used is qualitative. The type of research utilized is a case study, which involves an in-depth, detailed, and detailed investigation into a specific event or ongoing case. The data sources obtained in this study utilize primary data sources derived from interviews. The data collection method employed by the researcher is through direct interviews with informants. The findings of the research on the content of marriage guidance received from KUA Wonokromo include: (a) Patience to better control emotions, (b) Keeping silent to avoid conflicts, (c) Discussing together for clarity and finding appropriate solutions, and (d) Calming oneself to think clearly in making decisions. Second, the reasons why prospective couples participate in marriage guidance at KUA Wonokromo include: (a) Teaching mutual understanding towards spouses, (b) Building mental readiness for the next stage, and (c) Collaborating for mutual progress. Third, the practice of the values of a Sakinah family by married couples under the mentorship of KUA Wonokromo includes: (a) Building a harmonious family, (b) Being prepared to enter the marriage stage, and (c) Having physical and mental knowledge for the future.